1995
DOI: 10.1152/jappl.1995.78.2.449
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin synthesis blockade by ketoprofen attenuates respiratory and cardiovascular responses to static handgrip

Abstract: We investigated the effects of prostaglandin synthesis blockade on the changes in breathing pattern, mean blood pressure (MBP), and heart rate (HR) elicited by 3 min of static handgrip at 30% of the maximum voluntary contraction in 12 healthy volunteers. Before each handgrip trial, subjects were treated with intravenous administration of either saline placebo (control) or 1 mg/kg of ketoprofen. Muscle tension and integrated electromyographic activity of exercising muscles remained fairly constant during each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 0 publications
2
35
1
Order By: Relevance
“…The majority of studies in healthy humans have shown that inhibiting exercise-induced prostanoid synthesis attenuates reflex cardiovascular responses (7,8,14,23,25). These studies all used handgrip exercise, and they all administered either indomethacin or ketoprofen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies in healthy humans have shown that inhibiting exercise-induced prostanoid synthesis attenuates reflex cardiovascular responses (7,8,14,23,25). These studies all used handgrip exercise, and they all administered either indomethacin or ketoprofen.…”
Section: Discussionmentioning
confidence: 99%
“…The standard of care Rating of perceived exertion 0.5 kg 7 (6-9) 6 (6-9) 6 (6-7) 6 (6-7) 1.0 kg 9 (6-11) 8 (6-10) 7 (6-9) 7 (6-7) 1.5 kg 10 (8-13) 9 (8-13)* 8 (6-11) 7 (6-9) 2.0 kg 11 (9)(10)(11)(12)(13)(14) 10 (9-14)* 9 (7-12) 9 (7-10) 7.0 kg 15 (13)(14)(15)(16)(17) Data are shown as medians with ranges in parentheses; n ϭ 7 PAD patients and 7 healthy control subjects. *Significant difference between groups at the specific time point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with intra-arterial or intravenous infusions (4,11,15), local injections and oral intake of pharmacological substances (1), the presently used microdialysis technique with continuous infusion of NSAIDs allows for both a graded blockade as well as for maintaining steady-state situations over a long time period. In the present study an almost constant block was maintained from the end of exercise until 3 h postexercise (shown in Fig.…”
Section: Local Block Of Prostaglandin Synthesis By Microdialysismentioning
confidence: 99%
“…4 The triggering mediators responsible for the ergoreflex stimulation and their involvement in the abnormal exercise responses in CHF remain to be established. Different metabolic and humoral products have been studied in animals [7][8][9][10][11][12] and in humans, [13][14][15] but few investigators have investigated factors specifically involved in the ergoreflex overactivation of CHF patients. 16,17 One (or more) of these mediators may be involved as a link between alterations in muscle metabolism and/or hemodynamics present in CHF and the ventilatory response to exercise, via activation of muscle reflex.…”
mentioning
confidence: 99%